The Phenomenon of Body Shaming Among Students at Dehasen University, Bengkulu - Putri Afriyanti Dewi; Anis Endang; Yanto Yanto (Penerbit Jurnal Indonesia, 2023)
Body Shaming is physical violence that has an impact on psychology or mentality that can affect a person's life, both for individuals and groups. The large number of perpetrators who lead to body shaming causes negative impacts on victims, including depression, sadness and shame, and even withdrawal from social interactions. This study aims to determine the phenomenon of body shaming among students at Dehasen Bengkulu University. The type of research used in this research is descriptive qualitative. Based on the research results, researchers analyzed the phenomenon of body shaming among female students at Dehasen University Bengkulu through a critical approach to the theory of objectification of women. In this study the research informants were students at Dehasen University, Bengkulu City, who had shapes in the Body Shaming category, such as fat, tall thin, short fat (bontet), black skin, spotty faces. Through analysis of the data that has been obtained, researchers found that the act of body shaming experienced by the informant was the result of intersection between students, both classmates and close friends. The researcher saw that some informants experienced body shaming and had different impacts, namely creating the habit of monitoring their bodies regularly on themselves, feeling embarrassed, feeling insecure, becoming stressed thinking about this talk and distancing themselves from friends.